Reflections on research questions in mobile assisted language learning - Kukulska-Hulme Agnes (Journal of China Computer-Assisted Language Learning)
Research questions are central to mobile assisted language learning (MALL) projects and studies, yet they have received little attention to date. Taking research questions as its central focus, this paper offers some reflections on the complexity of the broader field of mobile learning, on different kinds of research, on salient themes and challenges in mobile learning and MALL, and it suggests some research directions for the future. Since MALL research is interdisciplinary, and since research questions are an object of study in other fields of knowledge, the paper refers to sources from multiple disciplines to support a more comprehensive consideration of current and future research questions in MALL. The paper is fundamentally an invitation to a global conversation about research questions in MALL.